The Effect of Nutrition Status Assessment Training on Cadres' Knowledge in Early Stunting Detection - A'in, Nurul; Budiastutik, Indah; Trisnawati, Elly; Marlenywati, Marlenywati (Institute Of Computer Science (IOCS), 2025)
Stuntingis one of the major challenges in public health in Indonesia, including in West Kalimantan.Stunting, which is characterized by a condition of failure to thrive due to chronic malnutrition and recurrent infections in early childhood, has long-term impacts on a person's physical, cognitive and productivity development. Based on the 2023 Indonesian Health Survey (SKI) report, the prevalence of stunting at the national level reached around 21.6%. This study aims to determine the Nutritional Status Assessment (PSG) of cadres' knowledge in conducting early detection of stunting in the community. PSG training is expected to improve cadres' knowledge in conducting early detection of stunting. The method used in this study was the Quasi Experiment One Group with a pre-test and post-test design. A total of 30 health cadres from the village were the samples in this study. Before the training, cadres' knowledge in early detection of stunting was tested using observation. The analysis used a paired sample t-test to determine any significant differences between cadres' knowledge before and after education on nutritional status. The results showed that there was a significant increase in cadres' knowledge in conducting early detection of stunting after participating in PSG training, with a p-value of 0.000. This shows that PSG training has a significant effect on increasing cadres' knowledge in detecting stunting. The conclusion of this study is that PSG training is effective in improving cadres' knowledge in early detection of stunting. It is recommended to strengthen the capacity of cadres in overcoming stunting in the community.